THE GENEALOGY OF MODERATE ISLAM IN THE SASAK PEOPLE’S RELIGIOUS EXPERIENCE - Dedy Wahyudin Sanusi (UIN Antasari Banjarmasin, 2022)
Tracing the root of moderate Islam within the Sasak people’s practices of life is the main concern of this article. It is factually seen that the Sasak people of Lombok, East Indonesia, practice all values of moderate Islam such as tolerance, balance, fairness, nationalism, and denying violence in the name of religion as an inseparable part of their lives. They practice Islam and tradition in the same breath-taking transcending any obstacles in their historical trajectory. This tenacious attitude, this article argues, is rooted in two points of Lombok people’s religious experiences: compatibility of their ancestor’s belief system and the extraordinary roles of Tuan Guru as the true driver of Sasak people’s minds and movements to stay permanently in the gold middle path of religious understanding and practice.